2009
DOI: 10.1074/jbc.m109.040725
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in Bcl-2 Pro-survival Proteins Determine Their Capacity to Bind Ligands

Abstract: Antagonists of anti-apoptotic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 61 publications
2
96
0
Order By: Relevance
“…The four signature hydrophobic residues of the Bak BH3 domain are buried within the groove (Fig. S5B), as in all previously determined BH3:prosurvival protein complexes (2)(3)(4)(5)27), and a salt bridge between a critical aspartyl residue on the peptide and an arginyl residue on the BH1 domain of the prosurvival protein, is also evident (Fig. S5C).…”
Section: Cellular Activity Of Proapoptotic Schistosome Bcl-2 Family Msupporting
confidence: 80%
See 2 more Smart Citations
“…The four signature hydrophobic residues of the Bak BH3 domain are buried within the groove (Fig. S5B), as in all previously determined BH3:prosurvival protein complexes (2)(3)(4)(5)27), and a salt bridge between a critical aspartyl residue on the peptide and an arginyl residue on the BH1 domain of the prosurvival protein, is also evident (Fig. S5C).…”
Section: Cellular Activity Of Proapoptotic Schistosome Bcl-2 Family Msupporting
confidence: 80%
“…Because BH3 mimetics function by engaging prosurvival proteins, we examined the ability of ABT-737 (the best characterized BH3 mimetic to date) to bind to sjA. Indeed, ABT-737 binds sjA with moderate affinity (IC 50 170 nM), whereas a closely related analog, W1191542 (27), binds significantly weaker (IC 50 5 μM), suggesting a highly specific interaction (Fig. 4A).…”
Section: Cellular Activity Of Proapoptotic Schistosome Bcl-2 Family Mmentioning
confidence: 99%
See 1 more Smart Citation
“…This could lead in turn to increased availability of free Bim for Mcl-1 binding in such cell types. However, other explanations cannot be excluded, including the possibility that drug treatment could directly affect the binding capacity between Bim and different antiapoptotic proteins (e.g., Bcl-2, Bcl-x L , and Mcl-1) that exhibit significant differences in the structural properties responsible for binding of BH3-only proteins including Bim (42). On the other hand, treatment with ABT-737 alone led to a slight decrease in amount of Bim coimmunoprecipitated by Mcl-1 in U937 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…48 At the periphery of proteins and solventexposed, interfaces are less subject to structural constraints, and Bcl-xL proved to be particularly flexible. 49 , 50 Transient pocket may also form on these surfaces. 51 Structural studies with Bcl-xL have shown that PPI inhibitors bind the large crevice receiving BH3 peptides, acting as competitive inhibitors.…”
Section: Resultsmentioning
confidence: 99%